Mechanisms and Treatments of Oxidative Stress in Atrial Fibrillation - Ren, Xiaomeng; Wang, Xiaofeng; Yuan, Mengchen; Tian, Chao; Li, Huilong; Yang, Xinyu; Li, Xinye; Li, Yanda; Yang, Yihan; Liu, Nian; Shang, Hongcai; Gao, Yonghong; et al. (Current Pharmaceutical Design, 2018)
Atrial fibrillation (AF) is a frequent cardiac arrhythmia. It is a common major cause of serious diseases and is an increasing health-care burden. AF is associated with an excess amount of reactive oxygen species. In this review, we summarize several possible reactive oxygen species pathways that induce AF based on atrial electrical and structural remodeling data. The sources and factors implicated in AF-related oxidative stress include NADPH oxidase activation, calcium overloading and mitochondrial damage, angiotensin system activation, nitric oxide synthase uncoupling, and xanthine oxidase activation-associated cardiovascular conditions. Scavenging oxidative stress markers and related substances are essential aspects of these molecular mechanisms, and may be a therapeutic target in AF.
Keywords: angiotensin